Exogenous ascorbic acid mitigates salt‐induced damage in soybean by modulating photosynthesis, antioxidant defense, and ionic homeostasis - Ajila-Celi, Gabriela Eugenia [UNESP]; Lata-Tenesaca, Luis Felipe; Calzada, Kolima Peña [UNESP]; de Cassia Alves, Rita; da Cruz, Mara Cristina Pessôa [UNESP]; Junior, José Sidnaldo Pinzetta [UNESP]; Carrega, Willians César [UNESP]; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2025)
Ascorbic acid (AsA) is one of the most abundant antioxidants, and can modulate several functions in plants under abiotic stress conditions. However, little is known about the mechanism of limiting harmful effects of salt stress through different exogenous AsA application methods. This study evaluated the effect of AsA application via a nutrient solution, foliar spray, and a combination there of on the adverse effects of salt stress in soybean plants. Two experiments using a 4 × 2 factorial scheme under a randomized block design included a salt-tolerant (M 8372) and salt-sensitive (M-Soy 8222) soybean cultivar. The plants of both cultivars were subjected to 0 and 100 mmol L−1 of NaCl and 0.85 mmol L−1 and 100 mmol L−1 of AsA via the root and leaves. Salt stress reduced the chlorophyll and carotenoid contents and photosynthetic rate and increased Na+ accumulation and lipid peroxidation in both cultivars. However, AsA application via the roots and leaves in M 8372 and leaves in M-Soy 8222 limited the adverse effects of salt stress by increasing the antioxidant activity of superoxide dismutase (SOD, EC 1.15.1.1), ascorbate peroxidase (APX, EC 1.11.1.11), and guaiacol peroxidase (GPOX, EC 1.11.1.7), as well as proline and endogenous AsA levels, thereby reducing Na+ accumulation in the tissues. In addition, AsA limited damage to the photosynthetic apparatus, as evidenced by the increased photosynthetic pigment content and photosynthetic rate, promoting plant growth. These results provide a new perspective on AsA delivery methods in soybean development under salt stress.
Keywords: Exogenous application; Glycine maxL; Oxidative stress; Salt stress; Sodium accumulation